PENGARUH KEPERCAYAAN DAN EMOSI DALAM ULASAN DARING MULTIMODAL TERHADAP KEPUTUSAN KONSUMEN - Herawati, Baiq Candra; Anggriani, Rini; Rahmatullah, Arwin Yafi (Universitas Prof. Dr. Hazairin SH, 2025)
This study aims to examine the influence of trust and emotional cues embedded in multimodal online reviews on consumer travel decision making. This study employs a systematic literature review approach. Data were collected from 115 empirical journal articles indexed in Scopus and Web of Science, published between 2023 and 2025. The review focuses on text, image, video, influencer, and live-stream-based online reviews related to consumer behavior in travel and service contexts. The findings indicate that trust related cues such as credibility, message consistency, and transparency significantly enhance consumers’ cognitive evaluations, while emotional engagement generated through visual and interactive content strengthens affective responses. The interaction of trust and emotion consistently influences purchase intention and visitation intention. Visual and interactive review formats intensify emotional immersion, whereas text-based reviews reinforce informational reliability. This study is limited to secondary data derived from published empirical studies and does not involve primary behavioral or experimental data. This research contributes to applied consumer behavior, digital marketing, and tourism studies by providing an integrated framework explaining how trust and emotion function across multimodal online review formats to influence consumer decisions.